Emergency Department (ED) Leaders' Perspectives on Offering HIV Preexposure Prophylaxis (PrEP) in New York City EDs: A Qualitative Study - Rael, Christine Tagliaferri; Mayorga, Stefanie; Gonzalez-Argoti, Tatiana; Ha, Lilian; Stonbraker, Samantha; Calderon, Yvette; Hoffman, Susie; Cowan, Ethan; Bauman, Laurie J.; Mantell, Joanne E. (The Journal of the Association of Nurses in AIDS Care, 2025)
Offering preexposure prophylaxis (PrEP) in nontraditional settings, such as emergency departments (EDs), may be an opportunity to connect HIV-vulnerable people with PrEP. Our study aimed to identify the perspectives of N = 10 ED leaders on initiating PrEP in EDs in New York City. Leaders completed 30-min, audio-recorded, in-depth interviews through Zoom, covering challenges/benefits to offering PrEP in EDs, and how potential programs could be set up and managed. From interviews, we formed three key discussion points for designing and implementing PrEP in EDs: (a) ED leadership views PrEP as important, but resource/contextual barriers pose an implementation challenge, (b) interventions must leverage familiar clinical pathways for implementation and minimize burden to provider time/ED resources, (c) using telehealth and patient navigators to implement PrEP in ED interventions could overcome the challenges but may not be available everywhere. Building on relationships with referral partners could be a viable alternative in resource constrained settings.